Yield And Seed Quality of Soybean (Glycine max (L.) Meru.) As Affected By The Application of Defoliants. - Prapto Yudono; R. C. Mabesa; G. O. San Valentin; B. B. Mabbayad (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1991)
-